2021
DOI: 10.1021/acsomega.1c05831
|View full text |Cite
|
Sign up to set email alerts
|

Green Degumming Technology of Hemp and a Comparison between Chemical and Biological Degumming

Abstract: This paper provides an efficient and environmentally friendly biochemical degumming method for hemp fiber, which can address the problems of high temperature, high pressure, and extreme pollution of the traditional chemical method and the harsh reaction conditions of biological degumming, such as a long reaction time and pH. In the biochemical method, dilute solutions of alkali pectinase lyase and chemical additives were used to process the hemp fiber and then the fiber composition and structure were investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The chemical auxiliaries provided by the patent acted on the fiber surface to cause the fibers to swell so that the released pectinase lyase could act on the pectin layer of the fibers more quickly to achieve the pectin removal effect rapidly. 20 The alkali content of the biochemical degumming solutions was 0.4% and the total content of salt was 0.8%, which is much less than that of reported chemical solutions with an alkali content of 10%. 21 2.2.3.…”
Section: Methodsmentioning
confidence: 69%
“…The chemical auxiliaries provided by the patent acted on the fiber surface to cause the fibers to swell so that the released pectinase lyase could act on the pectin layer of the fibers more quickly to achieve the pectin removal effect rapidly. 20 The alkali content of the biochemical degumming solutions was 0.4% and the total content of salt was 0.8%, which is much less than that of reported chemical solutions with an alkali content of 10%. 21 2.2.3.…”
Section: Methodsmentioning
confidence: 69%
“…It showed that pectin was greatly removed after the third alternating boiling cycle. By comparison, the obvious characteristic peak at 1740 cm –1 is shown in Figure e,f, after fourth and fifth alternating boiling cycle due to the hydroxyl group of cellulose formed carboxyl group during the esterification reaction in the fourth and fifth alternating boiling cycle, which made CNFs with hydrophobicity in the preparing process. , …”
Section: Resultsmentioning
confidence: 95%
“…By comparison, the obvious character-istic peak at 1740 cm −1 is shown in Figure 6e,f, after fourth and fifth alternating boiling cycle due to the hydroxyl group of cellulose formed carboxyl group during the esterification reaction in the fourth and fifth alternating boiling cycle, which made CNFs with hydrophobicity in the preparing process. 48,49 Figure 6 also showed that characteristic peak ranges from 1508 to 1243 cm −1 correspond to the benzene ring, which illustrated the removal effect of acid-insoluble lignin and cellulose extraction. The tensile vibration at 1250 cm −1 corresponds to the acetyl group which is cross-linked between lignin and hemicelluloses shown in Figure 6a.…”
Section: Chemical Structure Of Hemp Stalk Is Treated By the Different...mentioning
confidence: 82%
“…Biological solution preparation: 58 the following samples were prepared; 1.5% pectin lyase, 0.4% sodium hydroxide, 0.13% sodium carbonate, 0.17% sodium chloride, 0.13% calcium chloride, 0.03% sodium phosphate, 0.02% sodium formate, 0.2% sodium silicate, 0.13% sodium sulfite, 0.15% ethylene glycol, as well as distilled water of 97.0%. The solution was prepared in proportion; weak acid solution preparation: 59 5% sodium chlorite, 0.8% acetic acid, and 94.2% water in proportion; chemical solution preparation: 60 dilute 98% concentrated sulfuric acid to 54% H 2 SO 4 and cooled to ambient temperature.…”
Section: Methodsmentioning
confidence: 99%